Accounting information systems - Hall, James A. (Thomson Learning, 2001)
Accounting Information Systems, 3e provides thorough and up-to-date coverage of accounting information systems and related technologies. It features an early presentation of transaction cycles plus a special emphasis on ethics, fraud, and the modern manufacturing environment. The number-one Enterprise Resource Planning system, SAP, has been integrated into this new edition. Featuring screen shots of the SAP Web site in the text and a password that links students to a specially created SAP Web site, Hall is the only text on the market to give readers hands-on exposure to ERP. Also new to this edition are chapters on such cutting-edge topics as the Resources, Events, and Agents (REA) approach, Enterprise Resource Planning (ERP) systems, and Electronic Commerce systems. Hall assumes that the student is familiar with fundamental accounting principles and basic computer concepts and terminology and has been exposed to computer programming. The focus is on the needs and responsibilities of accountants as end users of systems, systems designers, and auditors